A reflection on the strategies and tactics of a non-governmental organisation: the case of the inner city resource centre - Tshuwa, Lesego Sebetlapelo Daphney (My University, 2016)
This research report is interested in telling the story of activist work by looking at the work that is done by the Inner City Resource Centre which is an NGO operating within the Johannesburg area. The intention of this study is to understand the effect of activism in an environment that is highly contested by reflecting on different viewpoints of those involved in inner city work and dynamics where housing is concerned. The views of different stakeholders working within this space therefore become highly critical. The narratives by the different individuals highlight the strategies and tactics employed by various actors and institutions in shaping processes in order to achieve goals.
Aiming to create a more just inner city of Johannesburg through activism--the case of the inner city resource centre
Research report submitted in partial fulfilment of the requirements for the Master of Science degree in Town and Regional Planning to the School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2016
Keywords: Non-governmental organizations--South Africa; Nonprofit organizations--South Africa; Social service--South Africa